Comparative analysis of transcriptomic profiling to identify genes involved in the bulged surface of pear fruit (Pyrus bretschneideri Rehd. cv. Yuluxiangli) - Ding, Baopeng (Physiol Mol Biol Plants, 2021)
Pear (Pyrus spp.) belongs to the genus Pyrus, in the family Rosaceae. Some varieties of pear fruit exhibit bulged surface, which seriously affects the quality and commodity value of the pear fruit. In this study, we performed anatomical, physiological, and transcriptomic analysis to explore the mechanism of paclobutrazol (PBZ) on the bulged surface of pear fruit. The vascular bundles of flesh were more evenly distributed, and the fruit cells were more compactly arranged and smaller in size treated with PBZ. However, the auxin (IAA) content of flesh was decreased in the treated group. Furthermore, the GO and KEGG analysis of differentially expressed genes (DEGs) showed that auxin, phenylpropanoid metabolic pathways, and transcriptional factor genes were significantly enriched on the relieved bulged surface of pear fruit. And it was analyzed that some genes contained auxin responded cis-elements from the selected DEGs in the promoter region. We conclude that PBZ plays a negative role in cell division, cell elongation, and vascular bundle development on the bulged surface of pear fruit through the involvement of auxin-related genes. This study will provide a theoretical basis for the regulation of the bulged surface of pear fruit by a growth retardant agent. SUPPLEMENTARY INFORMATION: The online version of this article (10.1007/s12298-021-00929-z) contains supplementary material, which is available to authorized users.